Свобода/воля як гідність в українській класичній драматургії ХІХ століття - Мороз, Л. (Слово і Час, 2018)
У статті простежується утвердження у творах українських драматургів (написаних після
відомого Емського царського указу 1876 р.) високих козацько-лицарських ідеалів свободи,
гідності, правди, честі. Наголошується на головній особливості художніх образів українського
козака-лицаря – спрямованості на захист свого поневоленого народу й України від численних
загарбників. The paper deals with the approaches of Ukrainian playwrights to the defining values that underlie
the Ukrainian national mentality: freedom, dignity, truth, honor, and faith.
Russian imperial authorities did not recognize the Ukrainians as a separate nation in the 19th century,
and struggled against “separatism”, in particular by forbidding the production of plays in Ukrainian,
the book printing, and even the importation of such books from abroad. Nevertheless the Ukrainian
authors ignored those prohibitions and instructions/demands to show only peasants and their lives on
the stage, and wrote works abundant in love for their native Ukraine and national self-respect, attention
to the history of Ukrainians and their struggle for freedom and dignity. These works contributed to
preserving the historical memory of the people and offered the specifi c Ukrainian perception of the
world. The artists used every opportunity to play performances, which created positive heroic images
of Cossacks-patriots, artistically interpreted complex problems in tragic historical situations.
Developing the traditions initiated by Taras Shevchenko, the authors contemplated the moral and political principles realized in the activities of the characters associated with Ukrainian history. (Some of them, such as Ivan Mazepa, Dmytro Vyshnevetskyi, are real historical fi gures; Gandzia and Sava Chalyi are semi-legendary persons; Tetiana Bondarivna is a heroine of the folk song.) These principles form the ideological and thematic essence of the two tragedies with the same title “Sava Chalyi” by M. Kostomarov and I. Tobilevych (I. Karpenko-Karyi), “Pereyaslav Night” by M. Kostomarov, “Bayda, Prince Vyshnevetskyi” by P. Kulish, and are also important in such works by I. Tobilevych as “Bondarivna”, “Gandzia”, “Mazepa”. A detailed analysis of the tragedies “Sava Chalyi” by M. Kostomarov and I. Tobilevych reveals that the romantic work of the former writer shows the character as a victim of circumstances and intrigues. In the realistic work of the latter playwright, it has been proved by artistic means that reaching a compromise in relations with an insidious conqueror is impossible, since such attempts lead an honest, trusting person to treason, and hence to dishonor. В статье идет речь о том, как утверждаются
в произведениях украинских драматургов (написанных после известного Эмского
царского указа 1876 г.) высокие казацко-рыцарские идеалы свободы, достоинства,
правды, чести. Акцентируется главная
особенность художественных образов украинского казака-рыцаря – направленность
на защиту своего порабощенного народа и Украины от многочисленных завоевателей.